1994
DOI: 10.1148/radiology.190.3.8115610
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in vertebral sizes in adults: biomechanical implications.

Abstract: Smaller vertebral bodies in women confer biomechanical disadvantages that may contribute to more vertebral fractures in elderly women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
114
1
6

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(136 citation statements)
references
References 0 publications
9
114
1
6
Order By: Relevance
“…In fact, when the absolute values of the cortical and trabecular densities were compared, they seemed to be virtually constant between players and controls, and across the bone sites, except the distal radius. This finding is similar to other CT studies where the volumetric density of cortical and trabecular bone has been shown to be fairly similar between children at different ages, and between men and women, 2,[15][16][17]36 and where the higher areal bone mineral density and ultimate bone strength in older children and men were due to larger bone size, not volumetric density of bone. In contrast to our study, Rico et al 33 found a significantly larger total and cortical volumetric density, but not trabecular density of the dominant distal radius, compared with the nondominant counterpart of sedentary right-handed adult subjects.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, when the absolute values of the cortical and trabecular densities were compared, they seemed to be virtually constant between players and controls, and across the bone sites, except the distal radius. This finding is similar to other CT studies where the volumetric density of cortical and trabecular bone has been shown to be fairly similar between children at different ages, and between men and women, 2,[15][16][17]36 and where the higher areal bone mineral density and ultimate bone strength in older children and men were due to larger bone size, not volumetric density of bone. In contrast to our study, Rico et al 33 found a significantly larger total and cortical volumetric density, but not trabecular density of the dominant distal radius, compared with the nondominant counterpart of sedentary right-handed adult subjects.…”
Section: Discussionsupporting
confidence: 90%
“…Concern about bone size and geometry, however, becomes relevant with patients of unusual size (either small or large), especially in situations where the bone size or geometry may change during the study, such as in studies of growing children or in those evaluating the effects of different exercise regimens on bone. 6,7,14,[15][16][17]19,25,39,40 The purpose of this study is to evaluate the characteristics of the upper extremity bones in male tennis players and their sedentary controls using peripheral quantitative computed tomography (pQCT). 38 We were especially interested in determining whether there were differences in bone size and geometry between the loaded and nonloaded arms of the players.…”
Section: Introductionmentioning
confidence: 99%
“…Both these variables (bone size and density) influence fracture risk. [12][13][14] Fracture risk is also dependent upon the geometry and architecture of particular skeletal sites. At the hip, prospective studies suggest that the length of the hip axis is positively associated with fracture risk, 15 and that this association is independent of bone density.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unknown whether patterns of osteophyte production are similar in males and females. Given that there are sex differences in age-related changes in bone mineral density in the vertebral column (2) and differences in the absolute and relative sizes of vertebral bodies (3)(4)(5), this merits further investigation. Other anatomical regions, including the pubic symphysis, have been shown to exhibit substantial sex differences in age-related changes (e.g., 6-8).…”
mentioning
confidence: 99%